Quantum entanglement criteria / Aini Syahida binti Sumairi - Sumairi, Aini Syahida (2013)
Entanglement of quantum is a quantum phenomenon which cannot be described using classical physics. This study reviews the quantum entanglement which discusses the various methods which are used to detect the entanglement. The properties of entanglement in the quantum system have been determined through the theoretical analysis of the quantities of nonclassical measure. That leads to the estimation of quantum entanglement with different parameters conditions. The study of the features and the nature of quantum entanglement enhance our understanding of the nature of entanglement processes. Furthermore, the entanglement is useful in the field of information processing where the entanglement is a basic ingredient of quantum information processing.